Inside the revolving door: campaign finance, lobbying meetings and public contracts : An investigation for Argentina - Freille, Sebastián (2018)
This paper explores the relationship between political influence actions and benefits obtained from public procurement. We develop a theoretical model of electoral competition where interest groups can engage in both ex-ante campaign contributions and ex-post lobbying contributions. We derive the optimal distribution of ex-ante and ex-post contributions by interest groups to candidates. If the preference of the interest groups are aligned, political contributions to both candidates are increasing in their respective announced expenditures. Ex-ante and ex-post contributions are imperfect substitutes and the higher the announced expenditure, the more biased the distribution is towards (ex-post) lobbying. Using previously unavailable individual-level data, we test empirically the predictions of the model and to model the probability of obtaining a public contract as a function of both ex-ante and ex-post efforts by interest groups.